Quantum Structures and the Nature of Reality The Indigo Book of `Einstein Meets Magritte' - Aerts, Diederik; Pykacz, Jaroslaw; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 1999)
Quantum Structures and the Nature of Reality is a collection of papers written for an interdisciplinary audience about the quantum structure research within the International Quantum Structures Association. The advent of quantum mechanics has changed our scientific worldview in a fundamental way. Many popular and semi-popular books have been published about the paradoxical aspects of quantum mechanics. Usually, however, these reflections find their origin in the standard views on quantum mechanics, most of all the wave-particle duality picture. Contrary to relativity theory, where the meaning of its revolutionary ideas was linked from the start with deep structural changes in the geometrical nature of our world, the deep structural changes about the nature of our reality that are indicated by quantum mechanics cannot be traced within the standard formulation. The study of the structure of quantum theory, its logical content, its axiomatic foundation, has been motivated primarily by the search for their structural changes. Due to the high mathematical sophistication of this quantum structure research, no books have been published which try to explain the recent results for an interdisciplinary audience. This book tries to fill this gap by collecting contributions from some of the main researchers in the field. They reveal the steps that have been taken towards a deeper structural understanding of quantum theory.
1. A Half-Century of Quantum Logic. What Have We Learned? -- 2. Quantum Mechanical Measurements -- 3. From Logic to Physics: The Logico-Algebraic Foundations of Quantum Theory -- 4. Non-Classical Logics, Non-Classical Sets, and Non-Classical Physics -- 5. Against (3z(BParadoxes(3y(B: A New Quantum Philosophy for Quantum Mechanics -- 6. Quantum Mechanics: Structures, Axioms and Paradoxes -- 7. Orthogonality Relations: From Classical to Quantum -- 8. Quantum Logical Semantics, Historical Truths and Interpretations in Art.s
Keywords: Algebra; Ordered algebraic structures; Quantum physics; Philosophy; Mathematical logic; Order, Lattices, Ordered Algebraic Structures; Quantum Physics; Philosophy, general; Mathematical Logic and Foundations